2009
DOI: 10.1136/sti.2009.035808
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of risk behaviour concurrent with links to other high-risk populations: a potentially explosive HIV epidemic among men who have sex with men in Guangzhou, China

Abstract: HIV has been introduced into MSM in Guangzhou. Demographic and behavioural risk factors and overlapping risk populations contribute to a potentially rapidly rising epidemic among MSM and the potential for a bridge to female partners in Guangzhou if timely and effective interventions are not implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 19 publications
(18 reference statements)
1
32
0
1
Order By: Relevance
“…About one-third of the studies reported the proportion of migrants (i.e., those without a permanent local residence) in their samples [17,23,26,29,32,[40][41][42][43][44], including one study that solely focused on migrant MBs [32]. The reported proportions of migrant MSM in those nonemigrant-exclusive samples ranged from 15.7 to 86.1%, with a median of 69.6%.…”
Section: Migratory Statusmentioning
confidence: 93%
“…About one-third of the studies reported the proportion of migrants (i.e., those without a permanent local residence) in their samples [17,23,26,29,32,[40][41][42][43][44], including one study that solely focused on migrant MBs [32]. The reported proportions of migrant MSM in those nonemigrant-exclusive samples ranged from 15.7 to 86.1%, with a median of 69.6%.…”
Section: Migratory Statusmentioning
confidence: 93%
“…6 Syphilis is now the second most commonly reported communicable disease in Guangdong province, 6 where a high prevalence has been observed among female sex workers 7 and men who have sex with men. 8,9 Mother-to-child syphilis transmission is an important public concern in epidemic areas because syphilis can cause spontaneous abortion, stillbirth and irreversible congenital defects. 10 These adverse outcomes are fortunately preventable through effective prenatal screening programmes.…”
Section: Introductionmentioning
confidence: 99%
“…Although HIV consulting and testing services are offered free in China, the HIV testing rates remain very low among Chinese MSM, only 30% of MSM report being ever tested (Choi, Lui, Guo, Han, & Mandel, 2006;He et al, 2009;Ruan et al, 2009). This intervention showed its potential to increase access to HIV consulting, testing and other related services.…”
Section: Discussionmentioning
confidence: 99%